2013
DOI: 10.1038/bjc.2013.212
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic role of KRAS, BRAF, PIK3CA and PTEN in colorectal cancer

Abstract: BackgroundMutations in KRAS, BRAF, PIK3CA and PTEN expression have been in focus to predict the effect of epidermal growth factor receptor-blocking therapy in colorectal cancer (CRC). Here, information on these four aberrations was collected and combined to a Quadruple index and used to evaluate the prognostic role of these factors in CRC.PatientsWe analysed the mutation status in KRAS, BRAF and PIK3CA and PTEN expression in two separate CRC cohorts, Northern Sweden Health Disease Study (NSHDS; n=197) and Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(109 citation statements)
references
References 43 publications
10
96
3
Order By: Relevance
“…Given that there is increasing evidence the BRAFV600E mutant microsatellite stable tumours are a particularly poor prognostic group, [22][23][24][25][26][27][28] we attempted to further stratify mucinous MMRp tumours on the basis of BRAF status. Interestingly, and perhaps unexpectedly, we found similar 5-year survival rates for BRAF wild type (57%) and BRAFV600E mutant (51%) MMRp mucinous colorectal cancers (P = 0.610).…”
Section: Discussionmentioning
confidence: 99%
“…Given that there is increasing evidence the BRAFV600E mutant microsatellite stable tumours are a particularly poor prognostic group, [22][23][24][25][26][27][28] we attempted to further stratify mucinous MMRp tumours on the basis of BRAF status. Interestingly, and perhaps unexpectedly, we found similar 5-year survival rates for BRAF wild type (57%) and BRAFV600E mutant (51%) MMRp mucinous colorectal cancers (P = 0.610).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that the incidence of BRAF mutations in right-sided colon cancer was increase compared with that in left-sided colon cancer [62,63]. Correlation meta-analysis revealed that BRAF mutation is a high risk factor for the prognosis of colon cancer [64]. The difference in genetic alterations between left-and the right-sided colon cancers should be further studied.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 96%
“…BRAF mutations, specifically V600E, which occur in less than 10% of patients with metastatic CRC, are associated with a poor prognosis (Richman et al, 2009;Van Cutsem et al, 2011). PIK3CA mutations are found in about 15% of CRC patients, and occur mainly in exon 9 and exon 20 (Roock et al, 2010;Garrido-Laguna et al, 2012), but their role as a biomarker of resistance to chemotherapy remains controversial (Mao et al, 2012;Eklöf et al, 2013). Thus, mutations in these genes may affect the prognosis of patients with PC from CRC.…”
Section: Introductionmentioning
confidence: 99%